2009
DOI: 10.1002/mrd.21013
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 deficiency impairs early pregnancy in mice

Abstract: Human oviductal cells produce complement-3 (C3) and its derivative, iC3b. These molecules are important in immune responses. Our recent study suggested that iC3b also possessed embryotrophic activity and it stimulates the blastulation and hatching rates of in vitro cultured mouse embryos. The objective is to study the impact of C3 deficiency on early pregnancy in vivo using homozygous C3-deficient (C3KO) and wild-type (C3WT) mice. C3 protein was undetectable in the reproductive tissues of C3KO mice. Deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…Moderate C3 expression levels in mice are necessary for successful gestation because C3 knock-out (KO) animals have a much higher resorption rate 15 days post coitum than their WT counterparts, due to trophoblast dysfunction and labyrinth development defects [49]. Our in vitro experiments suggested that FOXD1 mutations decreasing or increasing C3 expression are deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate C3 expression levels in mice are necessary for successful gestation because C3 knock-out (KO) animals have a much higher resorption rate 15 days post coitum than their WT counterparts, due to trophoblast dysfunction and labyrinth development defects [49]. Our in vitro experiments suggested that FOXD1 mutations decreasing or increasing C3 expression are deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…In C3-knockout mice, C3 has been found to be needed for successful pregnancy. C3-knockout mice had a lower rate of conception and the fetal reabsorption rate was higher, while the fetal and placental weights were lower in these mice (8). Furthermore, in mice the C3-regulator Crry was found to be crucial to a successful pregnancy (9).…”
Section: Discussionmentioning
confidence: 95%
“…A well regulated C system is a prerequisite for a healthy pregnancy (8,9). Recently, mutations in C regulatory genes have been reported in women with recurrent pregnancy loss (10).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent paper showed that C3 has a physiological role in early phases of pregnancy; C3-knockout mice have smaller blastocysts, higher resorption rates and smaller sizes of placentae [11].…”
Section: Complement Activation In Healthy and Aps Pregnancymentioning
confidence: 98%